Targeting the mTOR-Autophagy Axis: Unveiling Therapeutic Potentials in Osteoporosis - Rongjin Chen; Chenhui Yang; Fei Yang; Ao Yang; Hefang Xiao; Bo Peng; Changshun Chen; Bin Geng; Yayi Xia (Biomolecules)
Osteoporosis (OP) is a widespread age-related disorder marked by decreased bone density and increased fracture risk, presenting a significant public health challenge. Central to the development and progression of OP is the dysregulation of the mechanistic target of the rapamycin (mTOR)-signaling pathway, which plays a critical role in cellular processes including autophagy, growth, and proliferation. The mTOR-autophagy axis is emerging as a promising therapeutic target due to its regulatory capacity in bone metabolism and homeostasis. This review aims to (1) elucidate the role of mTOR signaling in bone metabolism and its dysregulation in OP, (2) explore the interplay between mTOR and autophagy in the context of bone cell activity, and (3) assess the therapeutic potential of targeting the mTOR pathway with modulators as innovative strategies for OP treatment. By examining the interactions among autophagy, mTOR, and OP, including insights from various types of OP and the impact on different bone cells, this review underscores the complexity of mTOR’s role in bone health. Despite advances, significant gaps remain in understanding the detailed mechanisms of mTOR’s effects on autophagy and bone cell function, highlighting the need for comprehensive clinical trials to establish the efficacy and safety of mTOR inhibitors in OP management. Future research directions include clarifying mTOR’s molecular interactions with bone metabolism and investigating the combined benefits of mTOR modulation with other therapeutic approaches. Addressing these challenges is crucial for developing more effective treatments and improving outcomes for individuals with OP, thereby unveiling the therapeutic potentials of targeting the mTOR-autophagy axis in this prevalent disease.